A nondominated sorting genetic algorithm for bi-objective network coding based multicast routing problems - Xing, Huanlai; Qu, Rong (Elsevier, 2013)
Network coding is a new communication technique that generalizes routing, where, instead of simply forwarding the packets they receive, intermediate nodes are allowed to recombine (code) together some of the data packets received from different incoming links if necessary. By doing so, the maximum information flow in a network can always be achieved. However, performing coding operations (i.e. recombining data packets) incur computational overhead and delay of data processing at the corresponding nodes.